(untitled) (Progressive Agriculture, 2013)
Experiments were conducted to develop and standardize the protocols of cryopreservation of sperm of Barbonymus gonionotus. Three extenders Alsevers solution, urea-egg-yolk and egg-yolk citrate and four cryoprotectants methanol, ethanol, DMSO and DMA were used. Cryodiluents were prepared by adding 10% cryoprotectant to 90% extender (% v/v). Milt and cryodiluents were mixed at a ratio of 1 : 9 for Alsevers solution and 1 : 4 for urea egg-yolk and egg-yolk citrate solutions. Alsevers solution with 10% DMSO showed the best performance and produced 78 ± 2.55% sperm motility at the post-thaw period. Urea egg-yolk and egg-yolk citrate with 10% DMSO produced 76 ± 1.87% and 74 ± 1.87% post-thaw motility respectively. When cryopreserved sperm was stored in liquid nitrogen for 130 days, a gradual reduction in motility ranging from 31.25 to 37.50% was observed. This could be happened due to frequent opening of the nitrogen dewar that could cause thawing of the sample. In breeding trials, sperm preserved with Alsevers solution and urea egg-yolk plus 10% DMSO produced 14.28 ± 7.06% and 15.46 ± 5.50% hatching respectively. In contrast, sperm preserved with egg-yolk citrate and 10% DMSO produced poor hatching as 8.01 ± 2.15%. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16863 Progress. Agric. 20(1 & 2): 117 124, 2009